Effect of extended cooking and oxygen prebleaching on the surface energy of Eucalyptus globulus kraft pulps - Carvalho, Maria da Graça Videira Sousa (2018)
The aim of this work was to investigate the influence of introducing an oxygen prebleaching stage and of extending the cooking process on the surface and papermaking properties of elemental chlorine-free bleached kraft pulps produced with Portuguese Eucalyptus globulus. Inverse gas chromatography was used to evaluate the surface energy as well as the Lewis acid/base character of the pulps, taking as reference one pulp cooked and bleached under standard conditions. The dispersive component of the surface tension, y~, was found to be highest for the pulp prepared under standard conditions, lowest for the pulp prepared by extended cooking and intermediate for the oxygen-prebleached pulp. Although all pulps exhibited a dominant acidic character (K)Kb > 1 ), the oxygen stage was found to enhance this character due to the higher surface concentration of oxygen-containing functional groups. Furthermore, oxygen prebleaching led to the formation of bulkier handsheets and it increased the beating energy. The opposite behaviour was found for the pulp produced by increasing the H-factor to extend the cooking.